(untitled) (Indian Journal of Animal Production and Management, 2015)
Ten Zovawk (Mizo local pig) female and two male pigs of 1st parity (4-5 months of age) were selected randomly from a sizable population maintained at Instructional Pig Farm of College of Veterinary Sciences & A.H., Aizwal, Central Agricultural University, Mizoram to study the performance under traditional housing system. The body weight changes of piglets up to 12 week of age showed a linear increase in growth. The conception rate in sows was 100%. Litter size at birth and weaning were 7.3± 0.67 and 6.1±0.71, respectively. The overall mortality was 14.29%. Out of that, 25% piglets died within first week after birth. There were no reports of mortality in piglets between 8-12 weeks of age and adult stages. The majority of pigs died due to respiratory distress associated with pyrexia. The profit/piglet was found to be Rs.611.76 which was remunerating for the rearing system in which farm labour and construction costs of sty were significantly low.